Validation and data characteristics of water vapor profiles observed by the Improved Limb Atmospheric Spectrometer (ILAS) and processed with Version 5.20 algorithm - Kanzawa, H.; Schiller, C.; Toon, G. C.; Sen, B.; Blavier, J.-F.; Park, J.; Bodeker, G. E.; Pan, L. L.; Sugita, T.; Nakamjima, H.; Yokota, T.; Suzuki, M.; et al. (Journal of Geophysical Research, 2002)
[1] Vertical profiles of water vapor concentration at high latitudes (57-72 degreesN; 64-89 degreesS) were observed by the Improved Limb Atmospheric Spectrometer (ILAS) solar occultation sensor aboard the Advanced Earth Observing Satellite (ADEOS). These measurements were made continuously from November 1996 through June 1997 with some additional periods in September to October 1996. A validation study of the water vapor data processed with the version 5.20 ILAS retrieval algorithm is presented in this paper. Uncertainty and general characteristics of the ILAS water vapor measurements are briefly reviewed. Comparisons are made with data obtained by (1) the ILAS validation balloon campaigns at Kiruna, Sweden and at Fairbanks, Alaska; (2) the aircraft measurements under the Photochemistry of Ozone Loss in the Arctic Region in Summer (POLARIS) campaign; and (3) available satellite measurements of the version 19 Halogen Occultation Experiment (HALOE) and the version 6 Stratospheric Aerosol and Gas Experiment II (SAGE II). The agreement between ILAS water vapor and all independent reliable correlative measurements in the altitude region of 15-60 km is better than 10% for the majority of cases and better than 20% for all comparisons, with the exception of some isolated cases detailed in this paper. Climatological comparisons of ILAS data with Upper Atmosphere Research Satellite (UARS) climatology and HALOE data show the overall consistency of ILAS water vapor data considering the known features of atmospheric circulation. The characteristics of ILAS measurements, i.e., high sampling frequency in polar latitudes with high vertical resolution along with the good data quality, make the ILAS water vapor data set valuable for various polar stratospheric research applications.